2019
DOI: 10.21470/1678-9741-2018-0270
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of "Coronary Artery Bypass Graft Angiography" with Right Transradial Access versus Left Transradial Access and Femoral Access: a Retrospective Comparative Study

Abstract: Objective Over the past 10 years, the rate of patients who have undergone coronary artery bypass graft (CABG) surgery has increased twofold in cases of coronary angiography. Today, transradial access is the first choice for coronary angiography. We aimed to compare the efficacy and reliability of radial versus femoral access for coronary angiography in post-CABG surgery in this study. Methods Data from 442 patients who underwent post-CABG surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Furthermore, the studies included in the meta-analysis are quite dated (only one study was published after 2005) and therefore precede widespread adoption of radial artery access. Balaban et al [ 23 ] found that femoral access is related to less fluoroscopy time, so LIMA visualization in the current practice may take longer time, but they also found that LIMA was best seen via the left radial route [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the studies included in the meta-analysis are quite dated (only one study was published after 2005) and therefore precede widespread adoption of radial artery access. Balaban et al [ 23 ] found that femoral access is related to less fluoroscopy time, so LIMA visualization in the current practice may take longer time, but they also found that LIMA was best seen via the left radial route [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Important scientific evidence has shown that interventionists currently prefer the right radial arteries, as the vast majority are right-handed, and angiography tables are generally designed on the right side, which makes manipulation safer and more comfortable (21) . This study has limitations, such as the scarcity of recent studies subsidizing the subject addressed.…”
Section: Discussionmentioning
confidence: 99%
“…TFA was better than lsTRA, which was also better than rsTRA in terms of fluoroscopy time (10.71 ± 1.65, 10.94 ± 1.25, 16.12 ± 5.28 min, p < 0.001) and total procedure time (17.28 ± 1.68, 17.68 ± 2.34, 23.04 ± 5.84 min, p < 0.001) and lsTRA was the most effective way for LIMA angiography. 20 …”
Section: Discussionmentioning
confidence: 99%